EUPHEMISM OF SURAH AL-BAQARAH IN THE HOLY QUR’AN - Nurhalimah Tamba; Anni Holila Pulungan; Amrin Saragih (Universitas Negeri Medan, 2018)
This study deals with euphemism of surah Al-Baqarah in the Holy Qur’an. It was aimed for investigating the types of euphemism used in surah Al-Baqarah, to describe realization of euphemistic expressions in surah Al-Baqarah, and to elaborate the reasons for realization of euphemism in surah Al-Baqarah. This study was conducted by using descriptive qualitative research. The data analyzed were sentence to sentence which contained euphemism. The source of the data was taken from Tafseer Ibn Kathir Vol 1-10 in the English language with Arabic verses. The researcher is the key instrument of the research. The result showed that there were 29 verses that contained of euphemism of surah Al-Baqarah. It divided into four concepts found in surah Al-Baqarah and one concept as new finding found in surah Al-Baqarah. Specifically, 1 (4%) for Shortening, 7 (23%) for Remodelling, 17 (59%) for Semantic change, 2 (7%) for Borrowing, and 2 (7%) for narrowing as new finding. The dominant types of euphemism of surah Al-Baqarah was Semantic change. It means that Muslim have to understanding and comprehending the meaning deeply. The ways of euphemism realized in surah Al-Baqarah, namely direct, indirect, implicit, and explicit. The reason euphemism realized in surah Al-Baqarah to soften a vulgar expression. In certain social contexts, they are used to avoid embarrassment and the direct mention of social taboos. In other situations, they are used to give more importance and a higher status to certain individuals and events.Keyword: Euphemism, Taboo, Surah Al-Baqarah